The impact of disclosing emotions on ratings of interpersonal closeness, warmth, competence, and leadership ability - Ludwig, Vera U.; Berry, Blaire; Cai, Jerry Y.; Chen, Nai Ming; Crone, Damien L.; Platt, Michael L. (Frontiers in Psychology, 2022)
Increasingly, business leaders and other professionals are called upon to be vulnerable and authentic in the workplace, which often includes disclosing emotions to others. While sharing emotions is known to enhance closeness, several questions remain underexplored. Specifically, disclosing personal facts about oneself and disclosing emotions have often been studied together, making it difficult to determine the effects of disclosing emotions per se. Moreover, not enough is known about factors that may influence effects of disclosing emotions, including recipients’ attitudes towards emotion-sharing, the sharer’s gender, and whether one considers the disclosure to be similar to one’s own experiences. We examined the impact of disclosing positive and negative emotion on ratings of closeness, warmth, competence, and leadership ability. 119 participants (95 female) in the US were shown headshots of individuals who were introduced in the first person in written format. For half of the pictures, an autobiographical fact about the individual’s past was disclosed. For the other half, an autobiographical fact and an associated emotion were disclosed. We found that sharing both positive and negative emotions increased feelings of closeness above and beyond the effects of autobiographical sharing alone. Sharing positive emotions also increased ratings of warmth, competence, and leadership ability. Male and female sharers benefited equally from disclosing emotions and effects were largely robust to recipients’ attitudes towards emotional expression. Having something in common with the disclosed fact or emotion further increased all ratings. These findings indicate that disclosing emotions may improve interpersonal interactions, with potential management applications in business.